Synthesis and Optical Characterization of Red-Emitting BaTa2O6:Eu3+ Phosphors - EKMEKÇİ, METE KAAN (SPRINGER/PLENUM PUBLISHERS, 2016)
Undoped and Eu3+ doped BaTa2O6 phosphors were synthesized via solid state reaction method and characterized by using XRD, SEM-EDS and photoluminescence (PL) analyses. The XRD results revealed that the crystal structure of BaTa2O6 allowed up to 10 mol% levels of Eu3+ ions due to the TTB characteristic network of adjacent octahedrals. SEM-EDS analyses confirmed the formation of BaTa2O6 structure and EuTaO4 secondary phase. BaTa2O6:Eu3+ phosphors exhibited orange and red emissions at 592.2 nm and 615.7 nm in the visible region respectively. The Commission Internationale d'Eclairage (CIE) chromaticity coordinates of the BaTa2O6:Eu3+ phosphors that excited at lambda (ex) = 400 nm ranged from orangish-red to pinkish-red depending on increasing Eu3+ concentration.
Keywords: BaTa2O6; TTB; Eu3+; Phosphors; Photoluminescence; LUMINESCENCE; PHOTOLUMINESCENCE; CHEMISTRY